Primary and Recurrent Breast Abscess in Non Lactational Women, Assessment of Risk Factors and Bacteria Involved. A prospective Cohort Study for Patients and Healthy Control - Abdul Wahed Dheeb, Israa (International Journal of Psychosocial Rehabilitation, 2020)
Background: Although inflammatory diseases of the breast are uncommon in non-lactational women, they pose a diagnostic and therapeutic dilemma with considerable morbidity. Diabetes mellitus, smoking, obesity, and low socioeconomic status are blamed for being risk factors for mastitis with the subsequent sequelae of breast abscess in non-lactating women. Polymicrobial infection, both aerobic and anaerobic bacteria, represents up to 40% of isolates in breast abscesses, predominantly in non-nursing women. Methods: From February 2012 to May 2019, eighty-nine patients attending the department of surgery at Al Diwaniyha Teaching Hospital with primary and recurrent non-lactational breast abscess were included in a prospective cohort study. Pus specimens were obtained at the time of drainage, which is subjected to Gram stain, Ziehl-Neelsen stain, and aerobic and anaerobic cultures. One hundred age-matched healthy females enrolled in the study as a control. Results: Breast abscess was more frequent in the age group 35-45 years. Smoking was found to be significantly more prevalent in patients than in controls, as 41.5 % of patients with breast abscesses were smokers as compared to 20% of controls. Diabetes was found to be significantly more prevalent in patients than in controls (24.7% vs. 8%). Forty-six percent of women with breast abscess had moderate to severe obesity. Only smoking and diabetes were found to be significantly more prevalent in recurrence (84.6% and 76.9%, respectively). p-value = 0.001... Mixed aerobic and anaerobic bacteria were the most common isolates (58.4%), followed by pure aerobic bacteria (12.35%), while pure anaerobic bacterial isolates came last (10.1%). Moreover, 17 (19.1 %) out of 89 breast abscesses were sterile, among which one was positive for AFB. Amoxiclav has the greatest activity upon the gram-positive aerobic cocci. Gram-negative bacteria were mostly sensitive to cephalosporin and ciprofloxacin. Metronidazole is still the most effective drug against anaerobic cocci and bacteroids. Conclusion: Smoking, diabetes, overweight/obesity, and a poor breastfeeding regimen all have strong associations with primary breast abscess. Only smoking and diabetes have a significant association with recurrent abscess. Mixed infection by aerobic and anaerobic bacteria predominates. Anaerobicocci the most isolated bacteria